2019
DOI: 10.1002/chir.23114
|View full text |Cite
|
Sign up to set email alerts
|

On the role played by the chirality of ligands on the aggregation of heterometallic CuII‐HgII complexes

Abstract: Copper(II) complexes constructed from enantiopure Schiff‐base ligands derived from o‐vanillin and methionine or from their racemic mixture have been employed as metalloligands towards mercury(II) ions. The nature of the heterometallic CuII‐HgII complexes (coordination polymers or oligonucler species), resulted from the reactions of the copper(II) complexes with HgCl2 or HgI2, is different. The enantiopure metalloligands lead to chiral coordination polymers, 1∞[{Cu(R‐/S‐valmet)(H2O)}2HgCl2]·5H2O·CH3OH and 2∞[{C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…These molecules contain uncharged amino groups at physiological pH that can be used to synthesize Schiff base ligands, molecules that play a key role in coordination chemistry. [32,33] Schiff base ligands are able to form stable complexes with most transition metal ions, which have received significant attention in bio-inorganic and medicinal chemistry since they may serve as models for biological important species and as potential cytotoxic and cytostatic agents. [34][35][36][37][38][39] The existence of metal centers bonded to biologically active molecules may enhance their activities.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules contain uncharged amino groups at physiological pH that can be used to synthesize Schiff base ligands, molecules that play a key role in coordination chemistry. [32,33] Schiff base ligands are able to form stable complexes with most transition metal ions, which have received significant attention in bio-inorganic and medicinal chemistry since they may serve as models for biological important species and as potential cytotoxic and cytostatic agents. [34][35][36][37][38][39] The existence of metal centers bonded to biologically active molecules may enhance their activities.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, amino acids have been used as molecular building blocks in this field. The advantages of this family of ligands are (i) the possibility of anchoring cations of different nature ( n s, n p, n d, and n f) in monodentate or chelating form by N -amino and O -carboxylate groups; (ii) the α position substituent being able to present different chemical functions, conferring additional donor centers or bulky template groups; and (iii) the possibility to functionalize the molecular structure to obtain modified linkers with higher coordination capabilities, conserving the chiral nature of the α-amino acid such as oxamate, , amides, oxamides, or oxalyl retro-peptide . In this sense, the α-amino acid Schiff base ligand ( aa -SB) is one of the most used strategies for the chemical obtainment of chiral ligands . Puntus et al reported the synthesis of two Eu­(III) mononuclear complexes [Eu­(PL-Asp)­(H 2 O) 4 ]·(H 2 O) and [Eu­(PL-His) 2 (H 2 O) 2 ]­Cl·(H 2 O) 4 based on two multidentate aa -SB’s starting from aspartic acid ( l -Asp) or l -histidine ( l -His) and pyridoxal (PL) .…”
Section: Introductionmentioning
confidence: 99%